Rapid climate‐driven loss of breeding habitat for Arctic migratory birds. (19th July 2016) - Wauchope, Hannah S.; Shaw, Justine D.; Varpe, Øystein; Lappo, Elena G.; Boertmann, David; Lanctot, Richard B.; Fuller, Richard A.
Abstract: Millions of birds migrate to and from the Arctic each year, but rapid climate change in the High North could strongly affect where species are able to breed, disrupting migratory connections globally. We modelled the climatically suitable breeding conditions of 24 Arctic specialist shorebirds and projected them to 2070 and to the mid‐Holocene climatic optimum, the world's last major warming event ~6000 years ago. We show that climatically suitable breeding conditions could shift, contract and decline over the next 70 years, with 66–83% of species losing the majority of currently suitable area. This exceeds, in rate and magnitude, the impact of the mid‐Holocene climatic optimum. Suitable climatic conditions are predicted to decline acutely in the most species rich region, Beringia (western Alaska and eastern Russia), and become concentrated in the Eurasian and Canadian Arctic islands. These predicted spatial shifts of breeding grounds could affect the species composition of the world's major flyways. Encouragingly, protected area coverage of current and future climatically suitable breeding conditions generally meets target levels; however, there is a lack of protected areas within the Canadian Arctic where resource exploitation is a growing threat. Given that already there are rapid declines of many populations of Arctic migratory birds, our results emphasize the urgency of mitigating climate change and protecting Arctic biodiversity.